Clinical outcome and vertical transmission variability among canine Neospora caninum isolates in a pregnant mouse model of infection - Dellarupe, Andrea (2013)
We compared the clinical outcome and vertical transmission of six canine Neospora caninum isolates using a pregnant BALB/c model. Four of the isolates were obtained from oocysts of naturally infected dogs (Nc-Ger2, Nc-Ger3, Nc-Ger6 and Nc-6Arg) and two were from diseased dogs with neurological signs (Nc-Bahia and Nc-Liv). The dams were inoculated with 2×106 tachyzoites of each isolate at day 7 of pregnancy. Morbidity, mortality and the antibody responses were evaluated in both the dams and the offspring, as was parasite transmission to the progeny. The mortality rates varied from 100% in Nc-Bahia and Nc-Liv-infected pups to 19% or less for those infected with the isolates from oocysts. The vertical transmission rates varied from 9 to 53% for N. caninum from oocysts, compared with 100% for the Nc-Liv and Nc-Bahia isolates. All dams showed specific IgG responses against tachyzoite and rNc-GRA7 antigens, confirming Neospora infection. The highest IgG levels were detected in mice inoculated with the Nc-Liv and Nc-Bahia isolates. These results demonstrate marked differences in virulence between the N. caninum isolates obtained from oocysts and neurologically affected dogs. This variability could help us to explain the differences in the outcome of the infection in definitive and intermediate hosts.